2020
DOI: 10.1101/2020.06.29.177386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germination response of diverse wild and landrace chile peppers (Capsicumspp.) under drought stress simulated with polyethylene glycol

Abstract: AbstractResponses to drought within a single species may vary based on plant development stage, drought severity, and the avoidance or tolerance mechanisms employed. Early drought stress can restrict emergence and seedling growth. Thus, in areas where water availability is limited, rapid germination leading to early plant establishment may be beneficial. Alternatively, germination without sufficient water to support the seedling may lead to early senescence, so reduced germinat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…originating from low precipitation environments may possess elevated tolerance to soil water deficit. For example, a recent germination study identified adaptive responses in chile pepper associated with precipitation [15]. Landraces from hotter, drier ecozones had significantly delayed germination, suggesting a possible adaptive response related to drought avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…originating from low precipitation environments may possess elevated tolerance to soil water deficit. For example, a recent germination study identified adaptive responses in chile pepper associated with precipitation [15]. Landraces from hotter, drier ecozones had significantly delayed germination, suggesting a possible adaptive response related to drought avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…However, this reduction in PBr with breeding is also reflected in our data where improved, US accessions had lower PBr. Bernau [ 18 ], using landraces from southern Mexico, indicated that PBr may relate to environmental adaptation. In her work, PBr was lower in chile pepper accessions from the wet, western coast of Oaxaca and higher in accessions from the drier ecozones, Eastern Oaxaca and the Yucatan peninsula, reinforcing our results.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the seven Mexican accessions from an array of chile peppers collected from diverse environments in the Mexican state of Oaxaca as potential sources of tolerance to water deficit based on a combination of their environment of origin, performance in a prior greenhouse study, and results from an environmental association analysis that used environment of origin as a “phenotype” [ 18 ]. In addition to their possible drought adaptations, the seven accessions serve as parents in on-going population development for continued genetic studies.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes the eggplant fruits are less developed or show smaller sizes compared to the actual size of the fruit. Under such circumstances sowing of crop in the late season or using heat tolerant hybrids as an alternative is advised under traditional breeding methods to reduce the damages caused by high temperature conditions [67].…”
Section: Breeding)mentioning
confidence: 99%
“…In certain rainfall areas the plants show certain rotting symptoms where the fruits of the eggplants become soft and oozes water from inside. In such cases of low temperatures and rainfall conditions the crops are sown in the later season, mixed cropping is employed sometimes or growing of the eggplants in green houses under controlled environmental conditions is the possible way to fix the changes in the climate [67].…”
Section: Breeding)mentioning
confidence: 99%